Pengaruh Waktu Hauling Terhadap Hasil Tangkapan Jaring Rampus (Bottom Gill Net) di Pelabuhan Perikanan Pantai (PPP) Bondet Kabupaten Cirebon Jawa Barat - Dirja Dirja; Erika Nur Fahmi (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2020)
This research was conducted for 3 months, from April to June 2019. The purpose of this study was to determine the effect of hauling time on the catch of the rampus nets at the Bondet Beach Fishery Port (PPP). Immersion of fishing gear is done for 30 minutes, the distance of fishing base to fishing ground takes 1-2 hours and the setting is done at 05.30 then the lifting net is done at 06.00. The research method used was experimental fishing, namely by conducting fishing operations in the sea using ramp nets. The results of the study are that the catches for 5 trips resulted in a trip number 1 of 13.84 kg in 120 minutes, trip 2 amounted to 5.97 kg in time 75 minutes, trip 3 amounted to 10.45 kg in 110 minutes , trip to number 4. From the results mentioned above and based on a simple Linear Regression Analysis it is obtained that the F count is 24.31 and the F table is 7.71 which means that the F count is greater than the F table. From this output we can know the calculated F value = 24.31 with a significant value F calculated> F table, then H0 is rejected and H1 is accepted which means there is a significant (significant) time variable (X) effect on the catch variable (Y). The regression equation is Y = -5,326 + 0,147 (X), where Y is the catch of X time (hauling). Thus every increase of 1 (one) minute X (time) will increase the variable Y (catch).